1996
DOI: 10.1063/1.471034
|View full text |Cite
|
Sign up to set email alerts
|

Energetics and kinetics of CO and NO adsorption on Pt{100}: Restructuring and lateral interactions

Abstract: Calorimetric heats of adsorption and sticking probabilities are reported for NO and CO on both the reconstructed hex and the unreconstructed ͑1ϫ1͒ surfaces of Pt͕100͖ by single crystal adsorption calorimetry ͑SCAC͒, at room temperature. The hex surface reverts to the ͑1ϫ1͒ structure during adsorption of both gases, as previously reported. The initial heat of adsorption on the ͑1ϫ1͒ surface is 215 kJ/mol for CO and 200 kJ/mol for NO. Adsorbate-adsorbate interactions determine not only the dependence of the heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
105
1
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(120 citation statements)
references
References 33 publications
12
105
1
2
Order By: Relevance
“…Experimental studies of NO temperature-programmed desorption and calorimetric measurements on different Pt surfaces have shown that lateral interactions are significant and cannot be neglected. 23,24 The strong repulsive interactions between the O-O and the O-NO pairs on Pt surfaces have been studied using first-principles calculations. [14][15][16]25,26 The through-space interactions are modeled herein by using a van der Waals (vdW) interaction model taken from the Merck molecular force field.…”
Section: Simulation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental studies of NO temperature-programmed desorption and calorimetric measurements on different Pt surfaces have shown that lateral interactions are significant and cannot be neglected. 23,24 The strong repulsive interactions between the O-O and the O-NO pairs on Pt surfaces have been studied using first-principles calculations. [14][15][16]25,26 The through-space interactions are modeled herein by using a van der Waals (vdW) interaction model taken from the Merck molecular force field.…”
Section: Simulation Methodsmentioning
confidence: 99%
“…The pre-exponential factor for bimolecular A* + B* surface reaction, where A* and B* are immobile, was calculated to be 10 -2 or 10 -3 cm 2 /s at 500 K and scaled by (T/500) 1/2 . 24 The deterministic rate equation for a bimolecular reaction system, however, must also be multiplied by the site density (10 15 sites/cm 2 ) in order to provide the pre-exponential factor in terms of s -1…”
Section: Reaction Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…49 There have been extensive discussions on the exact nature of the c͑4 ϫ 2͒ ordered structure, and other studies have suggested a different coverage of NO of 0.50 ML. 42,45,47,50 This coverage was proposed based on missing peaks in the LEED pattern, and the fact that on most other metals the saturation coverage of NO and CO is much higher than 0.25 ML. Notwithstanding these arguments we are of the opinion that the STM images presented in Ref.…”
Section: A Adsorption On the Fcc(100) Surfacementioning
confidence: 99%
“…For instance, Yeo et al 20 find, using calorimetric measurements, an adsorption energy of Ϫ1.94 eV for CO on Pt͕111͖, whereas Ertl et al 21 from isosteric measurements find Ϫ1.40 eV. The calorimetric measurements were performed for a series of Pt surfaces, including the Pt͕100͖-hex surface, 22 which makes, at least, comparison of the relative differences of the adsorption energies physically reliable and hence suitable to use in the fitting procedure. Unfortunately it is experimentally not possible to determine the difference in adsorption energy between the atop and bridge sites in a straightforward manner.…”
Section: A the Coõpt Systemmentioning
confidence: 99%